Conceptual model of the internationalization of medical education: Iranian faculty members’ perspective - Jazayeri, Sadaf; Akbari Javar, Hamid; Namaki, Ali; Ahmady, Soleiman (Researcher Bulletin of Medical Sciences, 2023)
Background and Objective: For about three decades, the internationalization concept has been crucial and necessary for medical education from the viewpoint of universities and the government. The "internationalization" definition depends on the educational conditions in related studies is not the same and indicated diverse concepts. Developing a conceptual model of medical faculties’ perspective is the first step to stimulating and localizing the internationalization program in Iran. Materials and Methods: A mixed-method was applied. Semi-structured interviews with experts were performed and an expert panel was formed by the snowball method. To complete the construction of the questionnaire, based on the experts' viewpoint, the internal consistency of the components was evaluated by Kendall's coefficient of concordance (W). The questionnaires were distributed randomly stratified selected 450 faculty members of medical universities and their responses were quantitatively analyzed using SPSS24 software. Cronbach's alpha index was applied to examine the reliability of the questionnaire-research tool. To identify the structural relationship between the components and dimensions, the method of Structural Equations with Partial Least Squares (PLS) was performed. Results: The developed conceptual model extracted and emphasis on two dimensions of at-home and cross-border. Conclusions: The model suggested that policymakers should consider internal and external internationalization dimensions and their seven rationales. Regardless of the higher significance of the external dimension, the hidden components of the internal dimension (in specific planning, and facilities/budget) demonstrated the highest impact factor on the internationalization of medical education.